Analysis of Regional Economic Stabilization Strategy of Southeast Sulawesi in the Era Nickel Industrialization - Jalaluddin Rum; Dita Damayanti; Muhammad Rofik; Muhammad Zulhijjah (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study examines the economic stabilization strategies implemented in Southeast Sulawesi during the nickel industrialization period, a crucial phase that significantly impacted the local and national economies of Indonesia. The main objective of the study is to analyze the various stabilization strategies used and evaluate their effectiveness in addressing the challenges arising from accelerated industrialization, particularly the fluctuations in nickel prices in the global market. The method used is library research, reviewing scientific literature, government reports, academic journals, and industry studies as relevant secondary data sources. The analysis shows that nickel industrialization has made positive contributions in the form of increased employment and infrastructure development, but also poses a number of serious challenges, such as environmental degradation, income inequality, and high economic volatility. This study recommends diversification of economic activities, increasing the capacity and skills of the local workforce, and implementing sustainable development policies as strategic steps to strengthen economic stabilization in the region. This study emphasizes the importance of a balanced approach to natural resource management so that economic growth does not sacrifice environmental sustainability and social justice. The research findings are expected to provide valuable insights for policymakers and stakeholders in designing and implementing adaptive and sustainable economic strategies in resource-rich regions such as Southeast Sulawesi. Overall, this research contributes to the understanding of how regions can manage the complexities of industrialization while maintaining economic stability and resilience.